Microbial- and thiosulfate-mediated dissolution of mercury sulfide minerals and transformation to gaseous mercury - Vázquez-Rodríguez, Adiari; Hansel, Colleen M.; Zhang, Tong; Lamborg, Carl; Santelli, Cara M.; Webb, Samuel; Brooks, Scott (Frontiers in Microbiology, 2015)
Mercury (Hg) is a toxic heavy metal that poses significant human and environmental health risks. Soils and sediments, where Hg can exist as the Hg sulfide mineral metacinnabar (β-HgS), represent major Hg reservoirs in aquatic environments. Metacinnabar has historically been considered a sink for Hg in all but severely acidic environments, and thus disregarded as a potential source of Hg back to aqueous or gaseous pools. Here, we conducted a combination of field and laboratory incubations to identify the potential for metacinnabar as a source of dissolved Hg within near neutral pH environments and the underpinning (a)biotic mechanisms at play. We show that the abundant and widespread sulfur-oxidizing bacterium Thiobacillus extensively colonized metacinnabar chips incubated within aerobic, near neutral pH creek sediments. Laboratory incubations of axenic Thiobacillus cultures lead to the release of metacinnabar-hosted Hg(II) and subsequent volatilization to Hg(0). This dissolution and volatilization was greatly enhanced in the presence of the sulfur intermediate, thiosulfate, which served a dual role by enhancing HgS dissolution and providing an additional metabolic substrate for Thiobacillus. These findings reveal a new coupled abiotic-biotic pathway for the transformation of metacinnabar-bound Hg(II) to Hg(0), while expanding the sulfide substrates available for neutrophilic chemosynthetic bacteria to Hg-laden sulfides. They also point to mineral-hosted Hg as an underappreciated source of gaseous elemental Hg to the environment.